The testamentary law of the Ancient world and Medieval European countries - Yermalovich, Viktar I. (Journal of the Belarusian State University. Law, 2019)
The subject of the article are the sources of the law countries of the Ancient world and the law of medieval European countries regulating succession procedure under the will. The process of studying the main institutes of succession law of the Ancient world and the law of medieval European countries has been carried out on the basis of the comparative analysis of law norms of the Ancient Babylon and Rome, Eastern Roman Empire, Serbia, the Great Princedom of Lithuania, Russia and Jemoit, the Russian states, Poland, Czech, France, Sweden. Analyzed is succession procedure according under the will the rights and obligations of a successors and a testators. The analysis of the norms of succession according to the law, made by the author of the article is based on the voluminous and authentic factual material.